Idiopathic Splenic Artery Pseudoaneurysm Rupture as an Uncommon Cause of Hemorrhagic Shock - Richard A. Schatz MD; Stephen Schabel MD; Don C. Rockey MD (SAGE Publishing, 2015)
Splenic artery pseudoaneurysms are infrequently encountered but critical to recognize. Limited literature to date describes associations with pancreatitis, trauma, and rarely peptic ulcer disease. Hemorrhage and abdominal pain are the most common manifestations. There is typically overt gastrointestinal blood loss but bleeding can also extend into the peritoneum, retroperitoneum, adjacent organs, or even a pseudocyst. Most patients with ruptured splenic artery pseudoaneurysms present with hemodynamic instability. Here, we describe a patient recovering from acute illness in the intensive care unit but with otherwise no obvious risk factors or precipitants for visceral pseudoaneurysm. He presented with acute onset altered mental status, nausea, and worsening back and abdominal pain and was found to be in hypovolemic shock. The patient was urgently stabilized until more detailed imaging could be performed, which ultimately revealed the source of blood loss and explained his rapid decompensation. He was successfully treated with arterial coiling and embolization. Thus, we herein emphasize the importance of prompt recognition of hemorrhagic shock and of aggressive hemodynamic stabilization, as well as a focused diagnostic approach to this problem with specific treatment for splenic artery pseudoaneurysm. Finally, we recommend that multidisciplinary management should be the standard approach in all patients with splenic artery pseudoaneurysm.